The quadratic isoperimetric inequality for mapping tori of free group automorphisms II: The general case - Bridson, M; Groves, D (2006)
If F is a finitely generated free group and φ is an automorphism of F then the mapping torus of φ admits a quadratic isoperimetric inequality. This is the third and final paper in a series proving this theorem. The first two were math.GR/0211459 and math.GR/0507589.